Implementation of digital technologies for managing the enterprise competitiveness based on benchmarking research - Valentina Pavlova; Inesa Chebavova (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет)
In the context of digital transformation and intensifying market competition, enterprise competitiveness depends increasingly on the ability to adopt innovative technologies and integrate best practices at the basis of benchmarking. The article aims to explore the implementation of digital technologies in the process of managing enterprise competitiveness based on benchmarking research. The methodology involves a comparative benchmarking analysis of financial indicators of industrial enterprise LLC “Pyatykhatsky Plant of Metallurgical Mixtures,” against key competitors. In addition, an expert survey was conducted to assess competitiveness parameters relevant to both internal and external stakeholders. The study reveals that despite relatively modest financial results, the enterprise demonstrates strong revenue efficiency per employee and high product quality. However, weaknesses were identified in marketing and client service capabilities. Benchmarking showed that leading competitors actively employ CRM systems and digital marketing tools. Based on these findings, a set of strategic recommendations was developed, including the introduction of basic CRM functionality, improved marketing communication, and enhanced service support. A reassessment based on expert evaluation showed a significant improvement in the company's competitiveness. The novelty of research lies in integrating benchmarking and stakeholder-based evaluation with competitiveness management system based at digital technology adaptation. Identifying opportunities for implementing artificial intelligence technologies in business activities and marketing is highly recommended. The study offers practical value for enterprises seeking to enhance their competitiveness through digital solutions.